Integrated watershed management solutions for healthy coastal ecosystems and people - Wakwella, Ama; Wenger, Amelia; Jenkins, Aaron; Lamb, Joleah; Kuempel, Caitlin D.; Claar, Danielle; Corbin, Chris; Falinski, Kim; Rivera, Antonella; Grantham, Hedley S.; Jupiter, Stacy D. (Cambridge Prisms: Coastal Futures, 2023)
Tropical coastal ecosystems are in decline worldwide due to an increasing suite of human activities, which threaten the biodiversity and human wellbeing that these ecosystems support. One of the major drivers of decline is poor water quality from land-based activities. This review summarises the evidence of impacts to coastal ecosystems, particularly coral reefs, from sediments, nutrients, chemicals and pathogens entering coastal zones through surface and groundwater. We also assess how these pollutants affect the health of coastal human populations through: (1) enhanced transmission of infectious diseases; (2) reduced food availability and nutritional deficit from decline of fisheries associated with degraded habitat; and (3) food poisoning from consumption of contaminated seafood. We use this information to identify opportunities for holistic approaches to integrated watershed management (IWM) that target overlapping drivers of ill-health in downstream coastal ecosystems and people. We demonstrate that appropriate management requires taking a multi-sector, systems approach that accounts for socio-ecological feedbacks, with collaboration required across environmental, agricultural, public health, and water, sanitation and hygiene sectors, as well as across the land–sea interface. Finally, we provide recommendations of key actions for IWM that can help achieve multiple sustainable development goals for both nature and people on coasts.